Model of best halal compliance practices in restaurants: a validation for excellence and differentiation - Azam, Md Siddique E; Ahmad, Anis Najiha; Abdullah, Moha Asri; Abdul Razak, Dzuljastri; Jaiyeoba, Haruna Babatunde (Penerbit UMT, 2025)
The study aims to provide insights into the essential components of halal compliance practises in restaurants through empirical research and to validate the "Best Halal Compliance Practice (BHCP)" model. A total of 320 halal-certified restaurants were surveyed and PLS-SEM analysis was adopted to assess the model. Out of thirteen hypotheses, only two were rejected. The findings justify the development of the BHCP model while contributing to minimising the research gap in relevant fields of studies and pointing researchers in the right direction to better understand the essential components of halal compliance practises in restaurants. Businesses can have potential impact on their financial and non-financial performance through the halal compliance practises proposed in this study. The present study is the first of its kind to investigate the relationship between different components of halal compliance and the overall halal compliance performance of restaurants (i.e., BHCP).